Teror Bom Buku di Jakarta Peran Polri dalam Penanganan Terorisme di Indonesia - Widodo, H.M.S. Urip (Jurnal Keamanan Nasional, 2016)
This research purposes to explain a terror of book bombing which take place in Jakarta on March 15th 2011. Based on data of Police Investigation Report, it capables to give explanation chronologically of planning from terror of book bombing. This terror of book bombing is a new modus of terrorist in their activity whereas their target is an individual. If we see from the number of victim and the quality of explosion, it can not be compared with bomb which were placed on certain buildings, such as cases of bombings before. However its impact is similiar, even the terror of book bombing has reached psychological aspect of society. Fear and panic spread to reach household are illuminating the success of terror of book bombing. Referring to formal law in Indonesia, activity and person of terror of book bombing can be categorized as a criminal act of terrorism.